ANALYSIS OF SEDIMENT FRACTION AND ITS RELATIONSHIP WITH CONCENTRATION OF HEAVY METALS IN SEDIMENTS IN COASTAL SEA WATER IN PARIAMAN CITY - Tri Radiko Felik; Rifardi Rifardi; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This research was conducted in February-March 2019. Purpose of this study was to determine sediment fraction, concentrations of heavy metals (Cu and Zn) in sediments, and the relationship of grain size of sediments with concentrations of heavy metals (Cu and Zn) in sediments in coastal marine waters of Pariaman City. The method used is the survey method, by determining the location of the sampling point by purposive sampling where the sampling location consisted of 3 research stations and each station consisted of 5 sampling points. The results showed that sediment types in the form of sandy mud and mud with an mean size (Mz) 5,317-7,267 Ø with the classification of coarse silt to fine silt, sorting 0,76-2,39 Ø showed the sorting of moderately to very poorly sorted sediments, skewness (-0,351) - (-0,919) with the classification of sediment grains tend to be very coarse skewed, kurtosis 0,49-10,24 indicates that energy works change and are not the same everywhere. The average concentration of heavy metals in sediments (Cu) ranges from 10,64-12,28 mg / kg and (Zn) 49,39-50,06 mg / kg has not crossed the threshold. The average value of Contamination Factor (CF) Cu (0,190-0,219) and Zn (0,537-0,544), Polution Load Index (PLI) ranged from 0,319-0,345, and the Potential Ecological Risk Index (PERI) ranged from 1,487-1,641 indicating that heavy metals Cu and Zn in sediments with low levels of contamination, not contaminated, and do not cause ecological risks. The results of a simple linear regression show the relationship of mean size (Mz) of sediment with the concentration of Cu heavy metals (y = 3,3077 + 1,3738x with r = 0,5143) and Zn (y = 28.014 + 3.5534x with r = 0,5427) interpret the strength of the relationship moderate with the form of a positive linear relationship.